Vulnerability assessment of economic sectors with regard to organised crime - Klima, Noel (2008)
In pre-crime policy space risk assessment becomes more and more relevant for law enforcement intending to appraise the threat and the impacts of organised crime. Very often assessments are being approached from the perpetrator’s side. Starting from the environmental angle, in this paper we will present a future oriented method to ascertain the vulnerability of licit economic sectors concerning organized crime by focusing on the opportunities provided. By applying this method, it will be possible to assess and rank loopholes within economic sectors which could be exploited by organized crime. The developed approach is planned to be applied to the transport-, export/import- and catering sector and builds one pillar of a research project whose goal it is to appraise the dangerousness of organised crime in Belgium